Forma de organización comunitaria como modelo del buen vivir, memoria histórica de la comunidad de Eugenio Espejo de Cajas, cantón Otavalo, provincia de Imbabura. - Inlago Inuca, María Soledad (2011)
The present work is a historical systematization of Community sociorganizativo process Eugenio Espejo de Cajas community; Kayambi identified as an indigenous people rooted for its history, culture and self-organizing system; Additional challenges is to keep its identity, forms, own customs and also seek to improve the living conditions of its population. In Chapter I the framework of the different concepts that are part of Community sociorganizativo work process. In Chapter II the historical process of rebuilding community sociorganizativo experience, its generality, context and how to turn the establishment of its structures, institutions, principles, values ​​and relationships and problems facing the state systematize; this paper attempts to find out to what extent valid Community model and organizational structure at this time of environmental, economic, cultural and political crisis affecting societies. Chapter III would deal with the description and interpretation of the experience and proposals on strengthening the community process and coping strategies, although there limitations for promoting community life be established. Chapter IV reflection and analysis on the different lessons learned from this work, the internal problems of the community, external factors influencing the community organizational process, legal and political constraints, achievements that have had to be made whole Community life process, the establishment and operation of its structure based on its principles and community values.